Effects of Phubbing: Relationships With Psychodemographic Variables - Ergün, Naif; Göksu, İdris; Sakız, Halis (Psychological reports, 2020)
The aim of this research is twofold: First, to adapt the Generic Scale of Phubbing and the Generic Scale of Being Phubbed into Turkish language and culture. Second, to investigate the relationships between phubbing, being phubbed, and various psychodemographic variables including anxiety, depression, negative self, somatization, hostility, loneliness, life satisfaction, and phone use duration. The two scales were adapted to Turkish with high psychometric properties, and the original item numbers were preserved. Analysis of the associations between variables showed that (1) phubbing was associated negatively with loneliness and positively with all other variables; (2) there was a strong relationship between phubbing and phone use duration; (3) somatization, satisfaction with life, and phone use duration predicted phubbing; (4) phubbing predicted all variables except satisfaction with life; (5) being phubbed was associated negatively with loneliness and satisfaction with life and positively with all other variables; and (6) anxiety, negative self, and hostility predicted being phubbed. This study is innovative for introducing two phubbing scales to Turkish and highlighting the psychological impact of phubbing on individuals.The aim of this research is twofold: First, to adapt the Generic Scale of Phubbing and the Generic Scale of Being Phubbed into Turkish language and culture. Second, to investigate the relationships between phubbing, being phubbed, and various psychodemographic variables including anxiety, depression, negative self, somatization, hostility, loneliness, life satisfaction, and phone use duration. The two scales were adapted to Turkish with high psychometric properties, and the original item numbers were preserved. Analysis of the associations between variables showed that (1) phubbing was associated negatively with loneliness and positively with all other variables; (2) there was a strong relationship between phubbing and phone use duration; (3) somatization, satisfaction with life, and phone use duration predicted phubbing; (4) phubbing predicted all variables except satisfaction with life; (5) being phubbed was associated negatively with loneliness and satisfaction with life and positively with all other variables; and (6) anxiety, negative self, and hostility predicted being phubbed. This study is innovative for introducing two phubbing scales to Turkish and highlighting the psychological impact of phubbing on individuals.